2019
DOI: 10.3390/rs11101220
|View full text |Cite
|
Sign up to set email alerts
|

Heart ID: Human Identification Based on Radar Micro-Doppler Signatures of the Heart Using Deep Learning

Abstract: Human identification based on radar signatures of individual heartbeats is crucial in various applications, including user authentication in mobile devices, identification of escaped criminals, etc. Usually, optical systems employed to recognize humans are sensitive to ambient light environments, while radar does not have such a drawback, since it has high penetration and all-weather capability. Meanwhile, since micro-Doppler characteristics from the heart of different people are distinct and not easy to fake,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…We can relate that to the superior accuracies achieved using the gait signature compared to other signatures, as in Ref. [ 2 ]. Additionally, a wide variety of deep learning structures are utilized for classification, with numbers of participants that range from 4 [ 33 ] to 100 [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can relate that to the superior accuracies achieved using the gait signature compared to other signatures, as in Ref. [ 2 ]. Additionally, a wide variety of deep learning structures are utilized for classification, with numbers of participants that range from 4 [ 33 ] to 100 [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increased demand for surveillance and security has accelerated research in human identification based on remote sensing technologies [ 1 , 2 , 3 , 4 , 5 ]. Radar, as a sensing modality, offers robustness and privacy compared to other technologies [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion artifacts and multisubject scenarios were not considered and remain a significant challenge for this approach. Recently, another study demonstrated the efficacy of radar-based identity authentication using a short-time Fourier Transform (STFT) [76]. Each person sat a 1.5 m distance and physiological signatures were recorded for about 6 seconds of the breathing pattern, using a 24-GHz continuous wave radar.…”
Section: Radar-based Identity Authentication Through Heart-based Featuresmentioning
confidence: 99%
“…Respiration rate (RR) and heart rate (HR) are critical physiological parameters for human beings, especially with respect to medical applications [1]- [3], life detection [4], and public safety [5]. Methods for obtaining the information can be divided into contact and noncontact measurements.…”
Section: Introductionmentioning
confidence: 99%